2014
DOI: 10.26877/malihpeddas.v2i1.496
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model Pembelajaran Role Playing Pada Mata Pelajaran Ipa Untuk Meningkatkan Hasil Belajar Siswa Kelas Iv Semester I Sd N Wonokerto 1 Karangtengah Demak Tahun Ajaran 2011/2012

Abstract: This study was to determine whether it can achieve the minimum criteria values kentusan, increased learning outcomes, student activity and performance of teachers on the subject of part of the plant structure and function in class IV Semester 1 Karangtengah Demak Wonokerto SDN Academic Year 2011/2012. The subject of this research were 35 students. The experiment was conducted in two cycles, each cycle comprising four phases: planning, action, observation, and reflection. The study was conducted in SDN Wonoketo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Furthermore, several research findings have found that techniques role playing can also be given in an effort to increase self-confidence (Andriati, 2015), improve learning (Djariyo, Mudzanatun, & Wijaya, 2012;Iskandar & Rachmadtullah, 2017;Sari & Rustiana, 2013;Zuraidah, 2017), increasing learning responsibilities (Sartono, 2014), improving self-concept (Rosidah, 2017), and preventing free sex behavior for students (Puspitaningrum & Indrawati, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several research findings have found that techniques role playing can also be given in an effort to increase self-confidence (Andriati, 2015), improve learning (Djariyo, Mudzanatun, & Wijaya, 2012;Iskandar & Rachmadtullah, 2017;Sari & Rustiana, 2013;Zuraidah, 2017), increasing learning responsibilities (Sartono, 2014), improving self-concept (Rosidah, 2017), and preventing free sex behavior for students (Puspitaningrum & Indrawati, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, efforts need to be given to students to help students reduce or even avoid academic procrastination. Implementing intelligent character education in a classical format (PKC-Ka) is considered one of the appropriate methods in reducing academic procrastination in students because intelligent character education in a classical format (PKC-Ka) is a learning method that can help students solve the problems they experience by thinking behavior that exists in themselves and in others through the roles they play and what they see so that they can identify situations that should exist in the real world which makes them ultimately change their behavior and attitudes in a more positive direction (Djariyo , Mudzanatun, & Wijaya, 2012). Therefore, by providing intelligent character education in the classical format (PKC-Ka), it is hoped that students will be able to manage behavior related to academic activities such as studying and doing assignments.…”
Section: Penthird Hypothesis Testmentioning
confidence: 99%